THE EFFECT OF MIND MAPPING TECHNIQUE IN STUDENTSâ€™ WRITING SKILLS OF NARRATIVE TEXT AT SECOND GRADE OF SMA SWASTA GKPI PADANG BULAN MEDAN - Simanjuntak, Christin Roria; Nadapdap, Febrianti; Sitanggang, Jelita; Sihombing, Rohani; Rahmawati, Rahmawati (Borneo Journal of English Language Education, 2020)
Writing is the most basic skill after reading. Writing can also express our ideas. What is in our brain, we can express it through writing. Human have 2 brains including, the right and left brains. The capacity of every human brain is very different. Some have hobbies such as drawing, singing, calculating and writing poetry. This research we conducted at SMA GKPI Padang BulanÂ  used mind mapping technique for students by writing narrative text. Where we only took 2 classes, including class XI IPA1 and XI IPA 2. This research aims to find several kinds of weaknesses in writing narrative text. Which method used in this research is quantitative data, instrument collecting data is an essay test which consists of 3 question. The researcher took the subject is a grade 11 students on the GKPI Padang Bulan private high school which consist of 27 students .